Systematic Literature Review: Team Performance and Psychological Factors Affecting Effective Collaboration in the Workplace - Aida Dwipriwanti; Yosi Mariana; F. Danardana Murwani; Ludi Wishnu Wardana (International Forum of Researchers and Lecturers, 2025)
Effective collaboration is a strategic imperative for contemporary organizations, yet its success hinges critically on team dynamics and underlying psychological factors like Trust and Psychological Safety. The purpose of this Systematic Literature Review (SLR) was to synthesize empirical research published between 2020 and 2025 to clarify how these psychological factors influence collaboration and team performance. Following the PRISMA guidelines, a rigorous search on Google Scholar using keywords such as